Economic responsiveness in organisational psychology curricula - Van Niekerk, Roelf (Rhodes University, Faculty of Education, Centre for Higher Education Research, Teaching and Learning, 2009)
This study focused on a topic at the intersection of two contexts, namely curriculum responsiveness and industrial/organisational psychology (IOP). The rationale for this study is based on two considerations. Firstly, a review of the IOP curricula offered at ten prominent South African universities revealed little overlap. This suggests that academic departments are not guided by shared principles when they implement decisions about the content or sequencing of curriculum content. Secondly, the Department of Education urges academics to design curricula that are relevant and responsive to contemporary conditions. These two considerations motivated the investigation of the following research question: What key performance areas (KPAs) do employers specify when they advertise positions suitable for IOP graduates? The investigation had two aims, namely (a) to systematically analyse the KPAs specified in job advertisements and (b) to compile KPA templates that may be used by IOP departments who wish to revise or transform their curricula. The research design of this study has five characteristics, namely that it is: (a) qualitative, (b) naturalistic, (c), descriptive, (d) applied, and (e) strategic. The study employed a purposive sampling strategy that involved the collection of documentary data (job advertisements aimed at recruiting IOP graduates) over a 52-week period (N=1115). The data was content analysed by means of a six-step documentary analysis method. Specific strategies were employed to enhance the validity of the findings. These strategies focused on credibility, transferability, dependability, and confirmability. Similarly, the ethical standing of the investigation was promoted by addressing four considerations, namely autonomy and respect for dignity, non-maleficence, beneficence, and justice. The data analysis procedure produced comprehensive and detailed qualitative descriptions of (a) 21 occupational categories, (b) 4070 KPA themes and (c) 84 KPA clusters. In addition, the number of occupational categories, KPA themes and KPA clusters were recorded and interpreted. In addition, the data analysis procedure produced comprehensive KPA templates that IOP departments may find useful. The templates reflect the KPAs specified by advertisements aimed at recruiting IOP graduates for a range of occupational categories and were designed to be used as benchmarks against which the economic responsiveness of curricula can be compared.
Keywords: Psychology, Industrial -- Study and teaching (Higher) -- South Africa; Universities and colleges -- Curricula -- South Africa; College graduates -- Employment -- South Africa